Molecular basis of protein S deficiency - García de Frutos, Pablo; Fuentes-Prior, Pablo; Hurtado, Begoña; Sala, Núria (Thrombosis and haemostasis, 2007)
Protein S deficiency (PSD) has been the most difficult to study among the classical inherited thrombophilic factors. This is in part due to the peculiar biology of protein S (PS), which has an anticoagulant role but no enzymatic activity, and because it interacts with plasma components that function in both haemostasis and inflammation. Clinically, it also has been difficult to define and standardise valuable assays to determine PS status and implication in thrombosis. Despite these drawbacks, at present heterozygous PS deficiency is well established as an autosomal dominant trait associated with an increased risk of thrombosis from data on familial and population studies. Almost two-hundred mutations have been characterised in PROS1, and approximately 30% of them have been characterised in vitro, clarifying the mechanisms leading to PSD. Furthermore, recent studies on the presence of large deletions in PROS1 have increased the number of PSD associated to PROS1 mutations. Finally, the discovery of new functions for PS, both in the anticoagulant system as well as in the interaction with cellular components through receptor tyrosine kinases, is broadening the importance of this molecule in the context of biomedicine.